2015
DOI: 10.1108/jfep-07-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

China’s shadow banking sector: beneficial or harmful to economic growth?

Abstract: Purpose – The purpose of this paper is to examine recent developments pertaining to China’s shadow banking sector. Shadow banking has the potential not only to be a beneficial contributor to continued economic growth, but also to contribute to systematic instability if not properly monitored and regulated. An assessment is made in this paper as to whether shadow banking is beneficial or harmful to China’s economic growth. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…The growth of SB and the inconclusiveness of the debate on SB prospects make studies addressing its implications on financial stability crucial. Some of the studies addressing such implications focused on specific components of SB (e.g., Culp 2013;Bengtsson 2013), and others addressed the overall SB sector (e.g., Barth et al 2015;Liang 2016a, Tsai 2016Zhou and Tewari 2019a, b;Ilesanmi and Tewari 2019). Bengtsson (2013) conducted a study on the European economy and reported that there is a lack of transparency regarding the composition of Money Market Fund (MMFs) assets making it difficult for European MMF investors to distinguish between MMFs based on their asset quality.…”
Section: Sb and Financial Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of SB and the inconclusiveness of the debate on SB prospects make studies addressing its implications on financial stability crucial. Some of the studies addressing such implications focused on specific components of SB (e.g., Culp 2013;Bengtsson 2013), and others addressed the overall SB sector (e.g., Barth et al 2015;Liang 2016a, Tsai 2016Zhou and Tewari 2019a, b;Ilesanmi and Tewari 2019). Bengtsson (2013) conducted a study on the European economy and reported that there is a lack of transparency regarding the composition of Money Market Fund (MMFs) assets making it difficult for European MMF investors to distinguish between MMFs based on their asset quality.…”
Section: Sb and Financial Stabilitymentioning
confidence: 99%
“…Nevertheless, Huang (2018) presented SB as the off-balance-sheet financing of traditional banks and reported that a limited level of risk-sharing does not improve financial stability. Barth et al (2015) conducted a study on the Chinese economy and stated that if the Chinese SB system encounters difficulties, such difficulties may also affect China's commercial banks. However, China's regulatory body has developed several policies for governing SB operations and the interconnectedness of SBs and commercial banks.…”
Section: Sb and Financial Stabilitymentioning
confidence: 99%
“…Studies of China’s banking sector largely conclude that its domestic SCM mirrors the US and European banking practices and opaque lending structures outside regulatory control in the pre-2007 period and, thus, significant downside risk that may destabilize the global economy ( The Economist , 2006, 2014, 2016a, 2016b, 2016c; Barth et al , 2015; Li et al , 2014; Li, 2014; Lu et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Money market funds ‫)8س(‬ hav‫؟‬ attracted considerable attention because of retail investor participation (Chernenko and Sunderam, 2014;Cipriani et al, 2013). Bengtsson (2016) Studies of China's banking sector largely conclude that its domestic SCM mirrors the US and European banking practices and opaque lending srtuctures outside regulatory control in the pre-2007 period and, thus, si^ificant downside risk that may destabilize the global economy {The Economist, 2^6, 2014Economist, 2^6, , 2016aEconomist, 2^6, , 2016bEconomist, 2^6, , 2016cBarth et al, 2015;Li et al, 2014;Li, 2014;Lu ‫(ة‬ ß¿, 2014).…”
mentioning
confidence: 99%
“…According to the Circular 107 issued by the Chinese government, shadow banking is defined as "credit intermediation entities and activities outside the traditional banking system"(Huang 2015). This definition, however, does not take into account the different risks and vulnerabilities attached to shadow banking such as the interconnectedness between formal banking system and shadow banks(Barth et al 2015, Lu et al 2015.…”
mentioning
confidence: 99%